Outcomes of a model for re-testing HIV-negative index contacts in Sedibeng, South Africa - Ditebogo L. Phiri; Kate Rees; Natasha Davis (AOSIS, 2023)
Background: Index contact testing is an HIV case-finding approach that elicits sexual or needle-sharing partners, as well as biological children, of people living with HIV (PLHIV) and offers them HIV testing services. Objectives: We aim to describe the results of an innovative project in Sedibeng District that expanded index testing by retesting previously negative contacts and incorporating status-neutral testing. Method: We used registers to identify people who previously tested HIV-negative through index testing from March 2019 to September 2021. The individuals were telephonically traced and offered HIV retesting. Data were collected on a weekly basis using REDCap®. We monitored the number of individuals called, those who came back for retest, and their HIV results. Results: Fifteen counsellors contacted 968 people over 12 months. Forty-eight percent (462 out of 968) of those called returned for testing. Of those, 121 (26%) tested positive. Overall, 66 out of 276 (24%) men with HIV and 55 out of 186 (30%) women with HIV were identified and linked to antiretroviral treatment (ART). Fifty-seven percent (194 out of 341) of clients who tested HIV-negative were offered, and 124 out of 194 (64%) initiated, pre-exposure prophylaxis (PrEP). All individuals who retested HIV-positive had a new diagnosis; none reported having had another positive test result between the original negative and the positive retest. Conclusion: Revisiting index clients with a previous negative HIV test result is worthwhile, creating an opportunity to identify undiagnosed PLHIV and high-risk people for PrEP. The high positivity rate highlights the importance of providing a sero-neutral approach to HIV testing, including integrating prevention messaging and linkage to PrEP services.